Application of the dental trauma guide of the international association of dental traumatology in a group of paraguayan dentists - Gamarra, José (2021)
Objective: To evaluate the application of the dental trauma guide according to the International Association of Dental Traumatology in a group of Paraguayan dentists from April to May 2021. The was a descriptive, cross-sectional, observational study. A group of Paraguayan dentists with internet access accepted to participate in the study. The measurement instrument was a closed questionnaire from Google Forms, distributed by instant messaging (WhatsApp) from January to April 2021. Based on the Guidelines for the Evaluation and Management of Traumatic Dental Injuries by the International Association of Dental Traumatology (IADT), the questionnaire includes 20 questions on the assessment of clinical and radiographic signs, determination of treatment variables, differentiation of the type of treatment, biological consequences of trauma, materials and splint time, and postoperative indications and medication. Results: 230 dentists participated; the mean age was 33 (SD = 6.4) years, 70.43% were women, 30.87% were general dentists, and 70.87% were practicing exclusively in private practice. 68.70% responded that they were familiar with the management and treatment of dentoalveolar trauma, while 70.87% had not heard or read about the IADT dental trauma guide. Regarding the level of knowledge, 60.00% scored an average mark. Conclusion: Most of the dentists surveyed had moderate knowledge regarding the evaluation and management of traumatic dental injuries.